2021
DOI: 10.1093/rpd/ncab140
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Lung Ct Protocol for the Diagnostic Evaluation of Covid-19 Lung Disease

Abstract: This study intends to evaluate the different lung CT scan protocols used for the diagnostic evaluation of COVID-19-induced lung disease in Iranian imaging centers in terms of radiation dose and image quality. After data collecting, subjective image quality, radiation dose and objective image quality such as noise, SNR and CNR were assessed. Statistically significant differences in effective dose and image quality were evident among different lung CT protocols. Lowest and highest effective dose w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… 36 , 37 Tabatabaei et al 38 revealed that low-dose chest CT is reliable in detecting COVID-19 pneumonia with a significant dose reduction. Similarly, Hosseini Nasab et al 39 showed that for assessing COVID-19 pneumonia, a range of tube currents of 20-50 mAs could produce acceptable chest CT images regarding radiation dose and diagnostic quality. Considering all these results, choosing the most appropriate CT protocol to reduce the radiation dose is crucial.…”
Section: Imaging Findings Of Covid-19 Pneumoniamentioning
confidence: 98%
“… 36 , 37 Tabatabaei et al 38 revealed that low-dose chest CT is reliable in detecting COVID-19 pneumonia with a significant dose reduction. Similarly, Hosseini Nasab et al 39 showed that for assessing COVID-19 pneumonia, a range of tube currents of 20-50 mAs could produce acceptable chest CT images regarding radiation dose and diagnostic quality. Considering all these results, choosing the most appropriate CT protocol to reduce the radiation dose is crucial.…”
Section: Imaging Findings Of Covid-19 Pneumoniamentioning
confidence: 98%
“…Several CT protocols for diagnosing and monitoring the course of COVID-19 and its treatment have been published since the beginning of the pandemic for a variety of CT scanners and vendors [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Quite often, protocols vary with regard to the associated radiation exposure and the desired image quality (IQ).…”
Section: Introductionmentioning
confidence: 99%
“…A Tomografia Computadorizada (TC) é um exame de imagens médicas baseado na interação de raios X com o corpo humano, seguida do processamento, por meio de algoritmos, que resulta na apresentação digital de imagens da anatomia estudada em diferentes vistas e planos seccionais. Essa técnica permite o diagnóstico de doenças, como a COVID-19, a avaliação de traumas, o estadiamento de tumores e o planejamento cirúrgico (Colégio Brasileiro de Radiologia, 2022;Nasab et al, 2021;Romans, 2011).…”
Section: Introductionunclassified